PETER BURKE, Exiles and Expatriates in the History of Knowledge, 1500–2000: Waltham (Mass.) 2017, Brandeis University Press / Historical Society of Israel, 294 s. - Čapská, Veronika (Dějiny – teorie – kritika, 2019)
Review.